Time to intravenous diuretic administration in patients hospitalized with heart failure: An observational study - Yasuyuki Shiraishi; Yuka Kurita; Hiromasa Mori; Kazuyuki Ooishi; Miyuki Matsukawa (ESC Heart Failure)
Abstract Aims To help establish optimized treatment strategies for congestion in patients with acute heart failure, this study aimed to provide a detailed summary of real‐world diuretic use in hospitalized patients with heart failure requiring urgent therapy in Japan. Methods and results This observational study used a Japanese medical records database to extract data of patients admitted to hospital with a heart failure diagnosis and an intravenous diuretic prescription from the day before admission to 2 days after. Time from hospital visit to first dose, second dose, and maximum dose of intravenous diuretics were determined. Patients were grouped according to whether they received diuretic modification, defined as an intravenous diuretic dose increase or concomitant use of other diuretics. Results Overall, 1577 patients were included in the study (without diuretic modification, n = 1140 [72.3%]; with diuretic modification, n = 437 [27.7%]). The study population was 49.5% female (n = 780) and the mean age ± standard deviation was 80.1 ± 12.7 years. Intravenous diuretic treatment was received within 1 h of their hospital visit in 43.5% of patients (686/1577) and ≤2 h in 16.4% of patients (258/1577). Among 437 patients with an inadequate response following their first dose, 42.1% received an intravenous dose titration, 56.5% received combination diuretics, and 1.4% received both. Over half of the patients (59.0% [258/437]) with diuretic modification received it after the first 24 h of the hospital visit. The median time from hospital visit to first dose titration was similar to time to first combination diuretic use (18.6 h and 17.0 h, respectively). The mean ± standard deviation duration of intravenous diuretic use was significantly longer for patients with versus without diuretic modification (6.3 ± 5.2 vs. 3.7 ± 3.2 days), and a significantly greater proportion of patients (44.6% [195/437] vs. 35.0% [399/1140]) received repeated intravenous diuretic administration. Other characteristics/outcomes of intravenous diuretic use were similar with versus without diuretic modification, including in‐hospital death (15.6% [68/437] vs. 13.9% [159/1140]) and mean ± standard deviation length of hospitalization (21.9 ± 14.7 days vs. 22.1 ± 21.2 days). Conclusions In Japan, real‐world patterns of intravenous diuretic administration for patients with heart failure remains far from the time‐sensitive approach recommended in Japanese, European, and United States guidelines.